Mollusks in the rocky tidal zone of the Phu Quoc island - Tuyen, Hua Thai (Vietnam Journal of Marine Science and Technology, 2021)
Results of the survey of mollusks in the rocky tidal zones at 22 sites along the Phu Quoc island in April 2019 has identified 42 taxa of Mollusks, belonging to 3 classes: Gastropoda (25 taxa), Bivalvia (16 taxa) and Polyplacophora (1 taxon). Species composition between stations varies from 2 to 9 species. The average density was 21.07 individuals/m2, ranging from 3.67 individuals/m2 in Southeastern Kim Qui to 84.22 individuals/m2 in Hon Dam Ngoai. Density of mollusks was highest in the middle tide zones (42.42 individuals/m2), followed by high tide zones (14.55 individuals/m2) and lowest in the low tide zones. Density dominance belongs to two species Patella sp. and Siphonaria sp. distributed in the middle tide zones.